Market risk exposure of merger arbitrage in Australia. (31st October 2011) - Hall, Jason; Pinnuck, Matthew; Thorne, Matthew
Abstract We investigate the risk‐return characteristics of merger arbitrage in the Australian market for corporate control, whereby hedge fund managers acquire companies subject to a takeover offer. On average, a strategy of buying target companies and short‐selling bidders making scrip offers would have generated an annual return of 30 per cent from 1985 to 2008, excluding transaction costs, compared to the return on the broader market of 12 per cent. However, performance is not market neutral, being positively associated with market returns during downturns and inversely related to market movements during rising markets. The payoffs to this strategy are analogous to a short straddle, whereby the investor is short a call and put option at the same exercise price. These results are consistent with large‐sample evidence from the United States and the United Kingdom and have not previously been documented in Australia, in which prior evidence is based only on cash deals during the 1990s.